Islamic tourism: An empirical examination of travel motivation and satisfaction in Malaysia - Mohamed Mohamed Kamal Moustafa Battour; Mohd Nazari Ismail; Moustafa Battour; Muhammad Awais (Taylor and Francis Ltd., 2024)
Indexed by Scopus